2020
DOI: 10.1093/scipol/scaa021
|View full text |Cite
|
Sign up to set email alerts
|

Orchestrating collaborative projects: Inside ICT networks in Horizon 2020

Abstract: This article investigates decisions taken at the project level in establishing and managing collaborative ICT projects under the European Framework Programme Horizon 2020. Based on interviews with project coordinators from European research organizations, we offer a detailed examination of how projects are built and managed, and how decisions influence the formation of collaborative networks. Projects are typically set up in three stages. In the first, a smaller group that has worked together before decides on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, related actions to disseminate and exploit project outcomes have mostly led to the development of scientific publications or patents rather than the transfer to practice [7,8]. Discussions on the ownership of results of European Framework Program (FP) projects show that academics want to publish as much as they can and industry partners mostly prefer to fill time-consuming patents [9]. Therefore, why not bring both actors together to develop a standard for the projects' tangible results?…”
Section: Introductionmentioning
confidence: 99%
“…However, related actions to disseminate and exploit project outcomes have mostly led to the development of scientific publications or patents rather than the transfer to practice [7,8]. Discussions on the ownership of results of European Framework Program (FP) projects show that academics want to publish as much as they can and industry partners mostly prefer to fill time-consuming patents [9]. Therefore, why not bring both actors together to develop a standard for the projects' tangible results?…”
Section: Introductionmentioning
confidence: 99%
“…The network coordination theory presents an effective approach to streamlining business processes within the networks of cooperating organizations, including supply networks [103]. In the literature, the coordinator is indicated, inter alia, as a key link in the marketing communication system of organizations cooperating in the region and country [104], an entity connecting the activities of cluster participants [105], as well as a network orchestrator [106], i.e., an entity combining the competences of various organizations for the implementation of network tasks, creating added value and generating innovative solutions. The coordinating function is also assigned to the flagship companies of the network [107].…”
Section: Discussionmentioning
confidence: 99%
“…With the aim to align the different countries under this common transformative vision, participation and access to this funding should be guaranteed and promoted by the research programmes to all countries especially those less involved in agroecology or having different agricultural goals or interests. Previous studies based on network theory ( Enger & Gulbrandsen, 2020 ; Protogerou et al , 2013 ) reported that few countries control access to the projects and related resources within European Framework programmes. An investigation of the degree of involvement of the different countries in European research projects related to agroecology as well as their networking and relations can help to highlight useful insights for the funders’ perspective.…”
Section: Introductionmentioning
confidence: 99%